FRI0060 A multi-biomarker disease activity blood test (vectra da) correlates with radiographic progression in early rheumatoid arthritis: results from the swefot trial. (23rd January 2014) - Hambardzumyan, K.; Bolce, R.; Cavet, G.; Chernoff, D.; Haney, D.; Forslind, K.; Petersson, I.; Geborek, P.; Ernestam, S.; van Vollenhoven, R. F.
Abstract : Background: In early rheumatoid arthritis (eRA), predictors of radiographic damage would be very useful for optimal targeting of available therapies. It has been suggested that combining various biomarkers may provide improved prediction. The multi-biomarker disease activity (MBDA) blood test has been validated as a measurement of rheumatoid arthritis (RA) disease activity. MBDA scores range from 1-100 and are based on 12 serum biomarkers: VCAM-1, EGF, VEGF-A, IL-6, TNF-RI, YKL-40, MMP-1, MMP-3, leptin, resistin, SAA, CRP. In the SWEFOT study, patients with eRA (symptom duration < 1 year) were started on methotrexate (MTX); at 3 months responders (DAS28 ≤ 3.2) continued MTX monotherapy and were followed in regular care, whereas non-responders were randomized to receive either triple DMARD therapy or the addition of infliximab. Objectives: To study the baseline MBDA score as a predictor of radiographic progression in eRA. Methods: Analyses were performed for 296 patients with complete clinical datasets consisting of baseline assessments of DAS28 (based on ESR), DAS28-CRP, CRP and the MBDA score using the validated algorithm; and for a subset of 235 patients that also had radiographs at BL and 1 year (assessed using the van der Heijde modified Sharp score [SvdH]). Spearman's correlation coefficients (r) were determined for the baseline MBDA score versus the change in SvdH over 1 year. Results: For the 296 patients, mean baseline values were: DAS28 = 5.7 and MBDA = 59. For the 235 patient-subset the mean baseline SvdH was 4.4 (median 2.0). Mean change in SvdH from BL to 1 year was 3.1 ± 6.0 (median 1.0). There was a significant correlation between baseline MBDA score and change in SvdH from baseline to 1 year: r = 0.271 (p<0.001); correlations of DAS28, DAS28-CRP, and CRP with change in SvdH were weaker: r = 0.063, 0.014, and 0.178, respectively (p=NS, p=NS, p=0.006). Correlations between BL MBDA and change in SvdH were similar and statistically significant when tested in month-3 responders (n=84) or non-responders (n=181) separately. Conclusions: In eRA patients treated initially with MTX, the MBDA score at baseline correlates significantly with radiographic progression during the first year, irrespective of whether the patient responds to MTX or not. Disclosure of Interest: K. Hambardzumyan: None Declared, R. Bolce Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, G. Cavet Consultant for: Crescendo Bioscience, D. Chernoff Shareholder of: Crescendo Bioscience, Consultant for: Crescendo Bioscience, D. Haney Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, K. Forslind: None Declared, I. Petersson: None Declared, P. Geborek: None Declared, S. Ernestam: None Declared, R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, MSD, Pfizer, Roche, UCB, Consultant for: AbbVie, BMS, GSK, MSD, Pfizer, Roche, UCB